Volatile profiling from thermal decomposition of Amadori compounds in the alanine-glucose Maillard reaction: An DFT insight of 3-ethyl-2,5-dimethylpyrazine forming mechanism - Pengxun Gao; Shang Wang; Baomin Feng; Chunying Liu; Yi Wang; Shaohua Dou; Liang Dong (Food Chemistry: X)
The composition of volatile compounds generated by the thermal decomposition of Amadori rearrangement products (ARPs) in the Maillard reaction between glucose and alanine was investigated by using a combination of thermal desorption cryo-trapping system and gas chromatography–mass spectrometry. A total of 25 volatile compounds were detected and identified, including 15 pyrazines, 3 pyridines, 1 pyrrole, and 6 complex nitrogen-containing compounds. The results indicated that pyrazines are the predominant products of the thermal decomposition of ARPs, and the specific formation temperatures of the various volatiles were determined. Additionally, density functional theory (DFT) was employed to study the formation mechanism of 3-ethyl-2,5-dimethylpyrazine in depth, and the structures of the reactants, transition states, and products were elucidated. Furthermore, by comparing the rate constants and reaction energy barriers of the different reactions, it was concluded that the synthesis of deoxyglucosones and the ring-forming reaction of pyrazines are the key reactions in the generation pathway of 3-ethyl-2,5-dimethylpyrazine.